2021
DOI: 10.1080/13696998.2021.1945242
|View full text |Cite
|
Sign up to set email alerts
|

The impact of seven major noncommunicable diseases on direct medical costs, absenteeism, and presenteeism in Gulf Cooperation Council countries

Abstract: Materials and methods:We used data from pre-existing datasets and the literature. We identified seven major noncommunicable diseases for which data were available: coronary heart disease, stroke, type 2 diabetes mellitus, breast cancer, colon cancer, chronic obstructive pulmonary disease, and asthma. We estimated the per unit cost (the annual cost of treating each illness for one person) of each disease, multiplied per unit cost by disease prevalence counts to generate disease-specific costs, and then summed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The study demonstrated that WRIs resulted in significant direct healthcare costs in Qatar; from 2011 to 2017, nearly 125 million USD was spent as direct healthcare costs to treat WRIs. This is almost double the combined annual direct medical costs for breast and colon cancer, as estimated for Qatar in 2019 [20]. Most of this expenditure was for the HLOS (58%), followed by the procedures performed during their treatment (39%).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The study demonstrated that WRIs resulted in significant direct healthcare costs in Qatar; from 2011 to 2017, nearly 125 million USD was spent as direct healthcare costs to treat WRIs. This is almost double the combined annual direct medical costs for breast and colon cancer, as estimated for Qatar in 2019 [20]. Most of this expenditure was for the HLOS (58%), followed by the procedures performed during their treatment (39%).…”
Section: Discussionmentioning
confidence: 95%
“…Cost analysis studies in WRIs are needed for the justification and planning of budgets, establishment of preventive and interventional programs and prioritization of research funding by healthcare policymakers. The overall healthcare costs in this study were estimated based on the incidence of the WRIs, analyzing data from the national trauma center that provides care for all cases with moderate and severe WRIs in the country, as this is one of the recommended approaches in health economics [18][19][20]. Medical costs are further classified into direct (types of payments and expenses) and indirect (resource utilization) costs.…”
Section: Discussionmentioning
confidence: 99%
“…While similar studies were focused on low/middle-income countries (LMICs), 42 43 relatively few studies have estimated the health and economic burden of NCDs in GCC countries, and fewer still have drawn comparisons between GCC countries. Our study expands on the most comprehensive studies to date on the burden of NCDs in GCC countries, 44 by using national data for morbidity, mortality and cost of treatment data where possible, and other data from other GCC countries as proxies where necessary (Finkelstein et al use international estimates only). 9 45 Finkelstein et al 44 found diabetes to contribute the most to the NCD burden, while our study finds CVDs to be the largest contributor.…”
Section: Discussionmentioning
confidence: 99%
“…Our study expands on the most comprehensive studies to date on the burden of NCDs in GCC countries, 44 by using national data for morbidity, mortality and cost of treatment data where possible, and other data from other GCC countries as proxies where necessary (Finkelstein et al use international estimates only). 9 45 Finkelstein et al 44 found diabetes to contribute the most to the NCD burden, while our study finds CVDs to be the largest contributor. This is likely due to the aforementioned differences in data sources, in addition to our study’s inclusion of premature death into the burden calculation.…”
Section: Discussionmentioning
confidence: 99%
“…We obtained estimates of the total direct cost, absenteeism cost, and presenteeism cost of the six diseases in Saudi Arabia for the year 2019 from a previous published study [ 16 ]. We obtained sex-specific prevalence rates for the year 2019 from the Global Burden of Disease database [ 17 ].…”
Section: Introductionmentioning
confidence: 99%